Microwave detectors based on the spin-torque diode effect - Prokopenko, O.V.; Slavin, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The spin-transfer torque (STT) effect provides a new method of manipulation of magnetization in nanoscale objects. The STT effect manifests itself as a transfer of spin angular momentum between the parallel magnetic layers separated by a nonmagnetic spacer and traversed by a dc electric current. The transfer of the spin angular momentum from one layer to another could result in the excitation of the microwave-frequency magnetization dynamics in one of the magnetic layers. On the other hand, when a magnetization dynamics is excited in a magnetic layered structure by an external microwave signal both the structure electrical resistance and current through the structure will acquire microwave components resulting in the appearance of a rectified dc voltage on the magnetic structure. This “spin-torque diode effect” can be used for the development of ultra-sensitive spintorque microwave detectors (STMD). Below we present a brief review of our recent work on the general properties of STMDs, analyze the performance of the “resonance-type” and “threshold-type STMD” and consider the possible applications for such microwave detectors.